Purification of Used Engine Oil by Pyrolysis– Adsorption Method Assisted Coal Activated Carbon - Alwathan, Alwathan; Mohd-Setapar, Siti Hamidah; Irwan, Muh.; Thahir, Ramli; Harjanto, Harjanto; Wahyudi, Wahyudi; Sirajuddin, Sirajuddin; Samosir, Damianus; Okko, Sarifudin; Ayu, Sekar; Toyo, Rahmat Budi; Fadilah, Muhammad Reza (Politeknik Negeri Ujung Pandang, 2024)
The increase in the use of engine vehicles every year is directly proportional to the amount of engine oil waste produced. Used engine oil is a class of hazardous waste that is harmful to the environment. This study aims to purify the base fuel from pyrolysis of waste engine oil by comparing integrated and non-integrated pyrolysis adsorption purification methods using activated low-rank coal as an adsorbent medium. The method used in this study is Pyrolysis using activated carbon from low-rank coal that has been carbonized with a temperature of 600 ° C and activated using H3PO4-NaHCO3. Pyrolysis is carried out by adding activated carbon with a ratio of 10% (w / w) of 11 grams from the volume of base fuel samples and Pyrolysis temperature of 350°C, then carried out by a variety of methods, namely the adsorption method followed by Pyrolysis, Pyrolysis followed by adsorption, and Pyrolysis adsorption integration. From this study, the optimum value of purification was obtained in the variation of integration adsorption pyrolysis with a density of 0.7631gr / ml and a specific gravity value of 0.7639 and an API degree of 53.7318, while for viscosity value of 0.5542 cP. The results of the product analysis have entered the standard specification value of gasoline or gasoline.